The Clash of Identity and Cultural Tradition in American Migrant Literature - Soghomonyan, Amalya (Bulletin of Yerevan University B: Philology, 2022)
The purpose of the article is to analyze the peculiarities of ethnic memory, eternal return and the American literary crater in the context of migrant literature. The article presents the clash of ethnic culture and super-culture motivated by ethnogenesis. The concepts of longing, identity, belonging, multiculturalism, otherness and exile help to reveal a number of psychological realities which the emigrant faces becoming a migrant. The preservation of the national genetic code is one of the most important issues for immigrants in the new environment. The article presents the types of migration based on the motivation, for example, voluntary or forced. In this case, the mental state of people is especially different, because the differences between migrations are in contrast with each other. Voluntary migrants have a clear motivation, certain plans and goals. On the contrary, forced migrants, as a rule, are demotivated, move against their will, have no plans, ideas about their own future and have no reason to continue living elsewhere. They are characterized by an uncertain and unclear condition.
Keywords: ethnic memory; American literary crater; eternal return; ethnogenesis; refugee; identity; belonging; existential choice; exile; alienation